Model Kepemimpinan Transformasional Nabi Muhammad SAW - Deswita, Elvi; Jamilus, Jamilus (ANWARUL, 2023)
As a person who will move and direct the organization in achieving its goals, the leader has a significant influence on an organization. There have been several disgraceful cases of leaders in educational institutions that have occurred in Indonesia, including. In September 2022 the Padang City Police, West Sumatra, examined 47 Special School Principals (SLB) in investigating corruption cases in the procurement of learning facilities and there was also the case of the school principal in Ogan downstream, South Sumatra, which slapped one class of students because of reports of students smoking in class. Based on this, it shows that the principal as the head of the institution is less professional in leading his institution, has not been able to carry out the leadership function properly, and does not yet have an ideal leadership spirit. The qualitative research method with the type of case study is the method used to write this article. The data collection technique used in this method is the Prophet Muhammad SAW's library research showing a leadership style that is in line with the latest leadership theory, transformational leadership, among these traits is having a high work ethic that upholds organizational interests above personal interests, cooperate in carrying out organizational activities, carry out the mandate that has been given with full responsibility, be disciplined at work, uphold unity and oneness, treat work as worship, and always build positive relationships with others.